2/3(x+4)=1/3(x+12)

Simple and best practice solution for 2/3(x+4)=1/3(x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3(x+4)=1/3(x+12) equation:



2/3(x+4)=1/3(x+12)
We move all terms to the left:
2/3(x+4)-(1/3(x+12))=0
Domain of the equation: 3(x+4)!=0
x∈R
Domain of the equation: 3(x+12))!=0
x∈R
We calculate fractions
(6xx/(3(x+4)*3(x+12)))+(-3xx/(3(x+4)*3(x+12)))=0
We calculate terms in parentheses: +(6xx/(3(x+4)*3(x+12))), so:
6xx/(3(x+4)*3(x+12))
We multiply all the terms by the denominator
6xx
Back to the equation:
+(6xx)
We calculate terms in parentheses: +(-3xx/(3(x+4)*3(x+12))), so:
-3xx/(3(x+4)*3(x+12))
We multiply all the terms by the denominator
-3xx
Back to the equation:
+(-3xx)
We get rid of parentheses
6xx-3xx=0

See similar equations:

| 1÷3=20÷d | | 4/9d+1/9=2/3 | | 4x-3(×-2)=21 | | 1.2x+13-8.7=50.5 | | 6x2+11x=2 | | 4(x-3)=-16;-1 | | 2x=1-(2-x)^1/2 | | 400=2x+2(2/3x) | | 3m=2m+3 | | 7x+6(7x+27)=-181 | | -3x+1=3+2x | | -19+4x-23=-2 | | 3=7–2s | | j+9=15 | | -2(2x-6)=-4(2x-10) | | 5/7x=23/14 | | 5(5t+1)=25t-7 | | 2t-3+t=30 | | (x-3)/7=(x+5)/6 | | --4/7=-2f/3 | | 2^2x=64 | | 4+2p=10(3-5p-2) | | -2(4a-3)=30 | | v+27=10v | | 4x=-8x-28 | | 2x+1/3-x-1/2=5/6 | | 7(s+5)^2-27(s+5)=4 | | 2(5k+5)=4(k+4) | | 4+2p=10(3-5p-2 | | 2x-5=11+4x | | 3x+5=4x+-9 | | 51=6+7n |

Equations solver categories